They can't kill us all : Ferguson, Baltimore, and a new era in America's racial justice movement - Lowery, Wesley, 1990- (Little, Brown and Company, 2016)
A behind-the-scenes account of the #blacklivesmatter movement shares insights into the young men and women behind it, citing the racially charged controversies that have motivated members and the economic, political, and personal histories that inform its purpose.